Advertisement Remove all ads

In the following example verify that the given expression is a solution of the corresponding differential equation: y = eaxxdydxyyeax;xdydx=ylogy - Mathematics and Statistics

Advertisement Remove all ads
Advertisement Remove all ads
Sum

In the following example verify that the given expression is a solution of the corresponding differential equation:

y = `"e"^"ax"; "x" "dy"/"dx" = "y" log "y"`

Advertisement Remove all ads

Solution

y = `"e"^"ax"`

∴ log y = log `"e"^"ax"` = ax log e

∴ log y = ax        .....(1) .....[∵ log e = 1]

Differentiating w.r.t. x, we get

`1/"y" * "dy"/"dx" = "a" xx 1`

∴ `"dy"/"dx" = "ay"`

∴ `"x""dy"/"dx" = ("ax")"y"`

∴ `"x" "dy"/"dx" = "y" log "y"`     ....[By (1)]

Hence,  y = `"e"^"ax"` is a solution of the D.E. `"x" "dy"/"dx" = "y" log "y"`.

Concept: Formation of Differential Equations
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×